TOWARDS A STATEMENT ON RESIDENTIAL GROUP CARE FOR CHILDREN AND YOUTH: A SUGGESTED FRAMEWORK - Anglin, James P.; Henderson, Bruce (International Journal of Child, Youth and Family Studies, 2025)
This contribution to the FICE35 Special Issue was constructed in the form of a draft statement, offering potential elements for organizations that may wish to counter the current movement opposing residential care for children and youth, which is now evident across Europe, North America and, increasingly, around the globe. The framework presented in this article was developed in response to a presentation by representatives of UNICEF at the FICE35 Congress in Split, Croatia, as well as the ongoing international campaign being waged against all forms of residential care for all ages of young people by UNICEF and a number of European and North American organizations, some of which are mentioned at the start of the article. The dimensions of quality for alternative care put forward in this document were also presented and discussed at a plenary panel on Quality in Alternative Care at the FICE35 Congress.